SOSIALISASI PENYAKIT MULUT DAN KUKU PADA PETERNAK DI DESA BLANG PALA KECAMATAN PEUSANGAN SELATAN - Yayuk Kurnia Risna; Chairul Fadli; Koji Al Adam; Sitti Zubaidah; Hariki Fitrah (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Aceh is the second largest province infected with Foot and Mouth Disease (FMD) in 2022. This has caused huge losses for farmers, thus the purpose of this community service was as a form of socialization of Foot and Mouth Disease (FMD) for breeders in Blang Pala Village, Peusangan Selatan District Bireuen Regency. The method of implementing service activities was carried out by counseling related to the material of characteristics and prevention of FMD as well as assisting biosecurity activities in cattle pens. This activity was said to be successful with an increase in the knowledge and understanding of the village breeders regarding the characteristics of FMD and how to control it through biosecurity. Increased understanding of FMD was also evidenced by the increased awareness of farmers regarding the vaccination program as an effort to prevent FMD. Thus, it is necessary to have continuity from the academic community of the Animal Husbandry Study Program, Faculty of Agriculture, Almuslim University.